Summary of Clinical Laboratory Studies Performed During Preclinical Safety Evaluation of Medicinal Products (Part II: Biochemical and Pathomorphological Studies) - A. V. Sorokina; S. V. Alekseeva; N. V. Eremina; A. D. Durnev (Регуляторные исследования и экспертиза лекарственных средств)
Chronic toxicity studies are an integral part of the overall toxicological evaluation of drug candidates. Biochemical studies of blood and urine serve to describe the general picture of the animal’s condition and to trace the dynamics of laboratory markers of organ damage after repeated administration of the drug — both for a group of animals, as well as individually. Pathomorphological studies of organs and tissues make it possible to understand the nature of damage at the cellular level. A systemic analysis of the data obtained allows for accurate identification of the body systems that are most susceptible to the toxic effect of the drug, as well as for assessment of the degree of impact and the reversibility of effects. Considering the great importance of the obtained pharmacological information, it is necessary to pay special attention to proper methodological implementation of all the stages of preparation and performance of the mentioned studies, as well as to proper analysis and interpretation of the data. The aim of the paper was to summarise the methodology of biochemical and pathomorphological studies based on the experience obtained in the Drug Toxicology Laboratory of the Federal State Budgetary Institute «Zakusov Institute of Pharmacology» when conducting chronic toxicity studies.